Rhizome and root anatomy of 14 species of Bromeliaceae1 - Proença, Suzana Lúcia [UNESP] (2008)
The anatomy of rhizomes and roots of 14 species of Bromeliaceae that occur in the cerrado biome were studied with the aim of pointing out particular anatomical features of the family and possible adaptations related to the environment. All the rhizomes are similar although some have root regions growing inside the cortex. In some species the vascular cylinder of the rhizome is clearly limited from the cortex. The roots are also very similar, although the coating tissue differs in roots growing inside the rhizome or externally to it and the cortex has a variable organization according to the region. The studied species present anatomical features that are associated to water absorption and storage, showing that they are adapted to the cerrado environment.